Bladder-sparing Radiotherapy for Muscle-invasive Bladder Cancer: A Qualitative Study to Identify Barriers and Enablers. Issue 12 (December 2017) - Walker, M.; Doiron, R.C.; French, S.D.; Feldman-Stewart, D.; Siemens, D.R.; Mackillop, W.J.; Booth, C.M.
Abstract: Aims: Bladder-sparing radiotherapy for muscle-invasive bladder cancer (MIBC) may be underutilised in North America. To understand factors driving practice we used the Theoretical Domains Framework (TDF) to identify barriers and enablers of bladder-sparing radiotherapy utilisation. Materials and methods: A convenience sample of Canadian urologists, medical oncologists and radiation oncologists participated in individual semi-structured 1 h interviews. An interview guide was developed using the TDF to assess barriers and enablers of bladder-sparing radiotherapy use. Interviews were recorded and transcribed. Two investigators independently identified barriers and enablers and assigned them to specific themes. Participant recruitment continued until saturation. Results: In total, 71 physicians were invited to participate and 34 (48%) agreed to be interviewed; 13 urologists, 11 radiation oncologists and 10 medical oncologists. We identified the following barriers to the use of bladder-sparing radiotherapy (relevant TDF domains in parentheses): (1) beliefs that radiotherapy has inferior survival compared with cystectomy (beliefs about consequences); (2) lack of referral from urology to radiation oncology (behavioural regulation; memory, attention and decision-making); (3) lack of 'champions' who advocate for radiotherapy (social and professional role); and (4) inadequate multidisciplinary collaboration (environmental context and resources). Predominant enablers to the use of bladder-sparing radiotherapy included: (1) 'champions' who believe in the value of radiotherapy (social and professional role); (2) beliefs by urologists that radiation oncologists should present radiotherapy options to all patients (social and professional role); (3) institutional policy that all MIBC patients should be seen by multiple specialists (environmental context and resources); (4) system facilitators of radiation oncology referral (i.e. nurse navigator) (environmental context and resources); and (5) patient-driven consultations seeking alternatives to cystectomy (social influences). Conclusions: These findings identify important barriers and enablers to the use of bladder-sparing radiotherapy in MIBC. Physician beliefs, access to multidisciplinary care and institutional context should be considered in efforts to increase the use of bladder-sparing radiotherapy. Highlights: Curative-intent radiotherapy for bladder cancer is underused in routine practice. This qualitative study explored barriers/enablers to radiotherapy use among clinicians. Physician belief that radiotherapy survival is inferior to surgery is a strong barrier. Other barriers include lack of referral to radiation oncology and lack of local radiotherapy 'champion'. Access to multidisciplinary care and institutional policy enables the use of radiotherapy.